Respuesta :
h=-3x^2-6x+5 subtract 5 from both sides
h-5=-3x^2-6x divide both sides by -3
(5-h)/3=x^2+2x halve the linear coefficient, square it, add it to both sides....
(2/2)^2=1 add 1 to both sides...
(5-h+3)/3=x^2+2x+1, now the right side is a perfect square...
(8-h)/3=(x+1)^2 multiply both sides by 3
8-h=3(x+1)^2 divide both sides by -1
h-8=-3(x+1)^2 add 8 to both sides
h=-3(x+1)^2+8
h(x)= -3(x+1)^2+8
Second answer down from the top :)
h-5=-3x^2-6x divide both sides by -3
(5-h)/3=x^2+2x halve the linear coefficient, square it, add it to both sides....
(2/2)^2=1 add 1 to both sides...
(5-h+3)/3=x^2+2x+1, now the right side is a perfect square...
(8-h)/3=(x+1)^2 multiply both sides by 3
8-h=3(x+1)^2 divide both sides by -1
h-8=-3(x+1)^2 add 8 to both sides
h=-3(x+1)^2+8
h(x)= -3(x+1)^2+8
Second answer down from the top :)